Long‐term mental health crisis among municipal public employees caused by the Fukushima nuclear accident and subsequent disasters: Questionnaire survey 10 years postdisaster - Noriko Setou; Yui Takebayashi; Tomoyuki Kobayashi; Naoto Nihonmatsu; Yutaka Matsui; Masaharu Maeda (PCN Reports)
Abstract Aim After the Fukushima nuclear accident in 2011, several municipal offices were forced to evacuate, and municipal public employees (MPEs) had to perform many administrative tasks related to the disaster. Typhoons and the COVID‐19 pandemic also affected the area afterwards. We conducted a survey for MPEs to investigate the mental health impacts and related factors. Methods This survey was conducted in the 10th year after the accident. Participants were MPEs working in the severely affected areas. We used a self‐administered questionnaire that included participants’ psychological distress (K6), experience during/after the disaster, job‐related stress, current problems, and the impacts of subsequent disasters. Based on K6 total scores, we analyzed factors related to mental health and the current problems among high‐risk MPEs. Results Of all the 775 participants, the number of high‐risk MPEs was 101 (13.0%) and many of those had comorbid suicide risk. Factors related to high‐score K6 were some individual‐related stress factors, including male and younger people, and some job‐related stress factors, including unaccustomed work and uncertainty about the future. The mental health status of MPEs in areas severely affected by the disaster has remained very serious more than 10 years later. Conclusion The problems and processes caused by the nuclear disaster, such as long‐term evacuation, were very specific compared to those of natural disasters. Compared to affected residents, MPEs could be more severely affected by the disasters over the long term. We consider it important to develop a mental health care system to prepare for future disasters.